Educating student teachers to apply the Guilford Structure of Intellect Model to induce active response learning in science classes in Jamaica - South-Guy, Ethel Maud (1981)
This study was motivated by the need to recommend to teacher educators in Jamaica an innovative strategy for teacher education, which could change teacher behaviour and, subsequently, engage students in an active response learning style. It sought to involve teacher trainees in a process of education in the cognitive ability categories of the Guilford Structure of Intellect Model, to the end that teachers could raise the level of thinking of students in science classes, from the passive accepting learners to more cognitive active participants in learning situations. The population for the study consisted of 144 high school students in Jamaica and 16 teacher trainees. After exposure to modular instruction, the eight experimental trainees applying the Guilford SI categories were involved in 15-minute interaction sessions with high school students in classrooms. These trainees applied the Serial-Centered Organization of Content and the Probe Technique. The control group teachers employed the traditional lecture approach to instruction. A naive group of eight students served as a second control group in the absence of a pre-test. Teacher probes and student responses for 48 instructional sessions were analysed. Significant change in teacher behaviour and subsequent student learning style were realized. Not only did the teacher trainees who applied the new strategy use more probes than their lecture counterparts, but they were able to record more elicited and spontaneous responses in the higher order cognitive levels than were possible in the traditional lecture group students
Keywords: Science education